Increased intraspecies diversity in Escherichia coli biofilms promotes cellular growth at the expense of matrix production - Azevedo, AS (2020)
Intraspecies diversity in biofilm communities is associated with enhanced survival and growth of the individual biofilm populations. Studies on the subject are scarce, namely, when more than three strains are present. Hence, in this study, the influence of intraspecies diversity in biofilm populations composed of up to six different Escherichia coli strains isolated from urine was evaluated in conditions mimicking the ones observed in urinary tract infections and catheter-associated urinary tract infections. In general, with the increasing number of strains in a biofilm, an increase in cell cultivability and a decrease in matrix production were observed. For instance, single-strain biofilms produced an average of 73.1 µg·cm-2 of extracellular polymeric substances (EPS), while six strains biofilms produced 19.9 µg·cm-2. Hence, it appears that increased genotypic diversity in a biofilm leads E. coli to direct energy towards the production of its offspring, in detriment of the production of public goods (i.e., matrix components). Apart from ecological implications, these results can be explored as another strategy to reduce the biofilm burden, as a decrease in EPS matrix production may render these intraspecies biofilms more sensitive to antimicrobial agents.